Evaluation of dilute acid pretreatment for bioethanol fermentation from sugarcane bagasse pith - Sritrakul, Nipat; Nitisinprasert, Sunee; Keawsompong, Suttipun (Agriculture and Natural Resources, 2017)
Sugarcane bagasse pith is the most abundant agricultural waste in Thailand and an attractive raw material for biosugar production using dilute acid pretreatment and enzymatic hydrolysis. In this study, the raw material was pretreated at 121 oC with different sulfuric acid concentrations (0%, 1%, 2%, 3% or 4% volume per volume, v/v) and pretreatment times (30, 60 or 90 min). The pretreated solid was hydrolyzed using a commercial enzyme (Celluclast® 1.5L). The maximum total sugars yield (53.7 g/100 g dry bagasse pith) was achieved at 1-2% v/v H2SO4 for 90 min, representing 67% of total sugars in the bagasse pith. For ethanol production, simultaneous saccharification and fermentation (SSF) and separate hydrolysis and fermentation (SHF) processes were employed using Pichia stipitis JCM 10742. The results indicated that both the ethanol concentration and productivity using SSF were higher than from the SHF process. The ethanol concentration and productivity using SSF were 3.70 g/L and 0.15 g/L/hr in 24 h fermentation, respectively, while for the SHF process the results were 2.58 g/L and 0.09 g/L/hr in 30 h fermentation, respectively.